Application Learning of Configuration Electron Chemical Elements - Saut Dohot Siregar (Jurnal Mantik, 2021)
Chemistry is a compulsory subject in high school, especially in the natural sciences department. In chemistry lessons, there are several sub-topics, one of which is the periodic system of electron configurations. Electron configuration relates to several other sub-topics. So that the electron configuration has an important role in the study of chemistry. The location of an element in the periodic table can be determined by determining the electron configuration of the element. So that the application of technology in helping students to understand electron configuration is needed. Intelligent computer assisted instruction is the application of artificial intelligence in the field of education that can be used to create more effective learning and can increase the willingness to learn and increase student motivation to learn. So it is necessary to make an application for learning the electron configuration of chemical elements. The resulting application has several learning support features, namely material, evaluation, discussion, and glossary. This application is built using the Fisher Yates Shuffle algorithm for randomization of numbers which is applied to practice questions. The application can run well on android devices version 4.4 or the latest version. Applications can measure students' mastery of learning materials more accurately. From the test results obtained 86% of respondents gave a positive response to the application that was built. Likewise, 60% of respondents expect further development. Either on the same material or on other chemistry materials to make learning more interesting and fun.